2012
DOI: 10.5098/fhp.v2.4.3004
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF TUBULAR Ni WICK USED IN LHP FOR SPACE APPLICATIONS

Abstract: Present research is focused on porous tubular wick development, which is considered as the heart of the Loop heat pipes (LHP) specifically used for space applications, such as satellites and space craft's. Basic purpose of a wick is to generate capillary pumping pressure required to transport a working fluid along a two-phase heat transfer loop. Wicking structures are generally made of wire meshes or sintered metal powders. Present work establishes Metal Injection Moulding (MIM) as a potential route for the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The model was also applied to the sintered wick and agreed well with the experimental results as well as with literature (the Supporting Information details the comparison of the sintered wick experimental data with the literature). The CuNW aerosponge samples exhibited excellent wicking behavior as compared to the sintered sample; the permeabilities of 2 × 10 −11 m 2 (4.5 mg cm −3 ) and 7 × 10 −12 m 2 (5.76 mg cm −3 ) are comparable to or higher than previously reported values for sintered wicks in the literature of 10 −13 –10 −11 m 2 , and much higher than the permeability of the experimentally fabricated sintered wick sample of 2 × 10 −13 m 2 . Sintered wicks are prevalent in many liquid transport and thermal management applications; thus, this comparison offers promise for use of CuNW aerosponges in heat pipes, particularly considering the potential reduction in materials required for heat pipe wick fabrication (CuNW aerosponges use as little as 0.1% of the copper required for sintered wicks) while maintaining liquid supply and therefore device cooling as indicated by the wicking performance.…”
Section: The Electrical Conductivities Of Cunw Aerosponges With Diffesupporting
confidence: 60%
See 1 more Smart Citation
“…The model was also applied to the sintered wick and agreed well with the experimental results as well as with literature (the Supporting Information details the comparison of the sintered wick experimental data with the literature). The CuNW aerosponge samples exhibited excellent wicking behavior as compared to the sintered sample; the permeabilities of 2 × 10 −11 m 2 (4.5 mg cm −3 ) and 7 × 10 −12 m 2 (5.76 mg cm −3 ) are comparable to or higher than previously reported values for sintered wicks in the literature of 10 −13 –10 −11 m 2 , and much higher than the permeability of the experimentally fabricated sintered wick sample of 2 × 10 −13 m 2 . Sintered wicks are prevalent in many liquid transport and thermal management applications; thus, this comparison offers promise for use of CuNW aerosponges in heat pipes, particularly considering the potential reduction in materials required for heat pipe wick fabrication (CuNW aerosponges use as little as 0.1% of the copper required for sintered wicks) while maintaining liquid supply and therefore device cooling as indicated by the wicking performance.…”
Section: The Electrical Conductivities Of Cunw Aerosponges With Diffesupporting
confidence: 60%
“…The process is very simple and low cost, the CuNW networks are assembled without specific crosslinking agent but with extraordinary properties. Furthermore, it was also found that CuNW aerosponges with different porosities and density distributions and different electrical and mechanical properties can be obtained just by tuning the initial composition and concentration of the reaction precursor, and the growth time and temperature for the synthesis process, making the method flexible for specific needs in various applications . One such application demonstrated in the present work is low‐density high‐performance wicks for fluid transport in heat pipes and other two‐phase thermal management devices.…”
Section: The Electrical Conductivities Of Cunw Aerosponges With Diffementioning
confidence: 77%
“…In this work, a Ni-wick prototype is prepared by novel Metal Injection Moulding (MIM) route in near-net shape with in-built vapour removal channels. Dimensions of the wicks were set to 15 mm and 10 mm for the outer and inner diameter, with total length of 45 mm (Samanta et al 2011). The fabrication of wicks would be affected by the following parameters: the property of the metal powders, fabrication method, sintering temperature and time and the sintering atmosphere.…”
Section: Fabricationmentioning
confidence: 99%
“…But it showed that these wicks may be produced with failures. Samanta et al [30] developed metal injection molding Ni wick structures and performed study on its physical characteristic depending on sintering time (30,60, and 90 min) and temperature (900, 930, and 950 C). Gernert et al [31] developed fine pore wick structure for LPH.…”
Section: Lhp Wick Structurementioning
confidence: 99%